See you soon: fixed-term contracts, unemployment and recalls in Germany—a linked employer–employee analysis - Oskar Jost (Empirica, 2022)
Almost 20% of all male employees in Germany who become unemployed return to their previous employers. Such temporary layoffs and the subsequent recalls are often used by firms to shift their labor costs onto society and the unemployment benefit system, which has led to various legislation aimed at prohibiting or reducing this undesired instrument in Germany. I analyze the interplay between fixed-term contracts, which can be used to undermine legal regulations, and temporary layoffs for men. For this purpose, I use comprehensive administrative data at individual level, complemented by various firm characteristics. My results show that unemployed workers who had previously worked on fixed-term contracts are more often recalled by their previous firms than workers who had permanent contracts. Moreover, older and low-skilled employees as well as migrants are particularly affected by the interplay between fixed-term contracts and temporary layoffs. This is also confirmed for women in an additional robustness analysis.
Keywords: J64; J65; J41; 330; Unemployment; Wage; Recall; Fixed-term contracts; Unobserved heterogeneity